School Trustees vs. Counsellor Educators: A Reaction to the Jevne Report - Eberlein, Larry E. (Canadian Journal of Counselling and Psychotherapy, 2012)
While the Jevne (1981) report reflects the view of guidance counsellors and educators, it is at variance with public expectations as outlined by the Canadian School Trustees Association. Educators and counsellors are reminded of the obligation they owe rate payers to provide the services for which they were hired.